2017
DOI: 10.1017/s0033291717002495
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in bipolar disorder: towards a dynamic understanding

Abstract: The present investigation illustrates real-world outcomes for QoL under guideline-driven BD treatment: improvements in mental QoL and decrements in physical QoL were observed. The data permitted investigation of dynamic interactions between QoL and symptoms, generating novel evidence for bidirectional effects and encouraging further research into this important interplay. Investigation of relevant time-varying covariates (e.g. medications) was beyond scope. Future research should investigate possible determina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Pharmacological [ 19 ] and non-pharmacological treatments [ 20 ] have been suggested to improve QoL in bipolar patients. A recent study from Canada reported an increase in mental QoL and decreases in physical QoL under guideline-driven treatment [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological [ 19 ] and non-pharmacological treatments [ 20 ] have been suggested to improve QoL in bipolar patients. A recent study from Canada reported an increase in mental QoL and decreases in physical QoL under guideline-driven treatment [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fifth edition of the Diagnostic and Statistical Manual of Psychiatric Disorders (DSM-5)5 states that the main features of BD are persistent episodes of mania and depression. Although this condition negatively influences the QoL of affected individuals6 and is a global source of disability, the biological basis of BD remains generally unknown, and the treatment of this disease is far from satisfactory 7. Objective cognitive functions, such as verbal memory and executive functioning as well as subjective cognitive functions, are often impaired in patients with euthymic BD 8,9…”
Section: Introductionmentioning
confidence: 99%
“…It is widely believed that personal satisfaction among BPAD patients is lower than predicted. Quality of Life is described as an individual's perception of their position in life in relation to the way of life and value systems in which they reside, as well as in relation to their goals, preferences, models, and concerns 20 .…”
Section: Discussionmentioning
confidence: 99%